IMMACULATE COLLECTION (THE) IMMACULATE COLLECTION (THE) (Rif. Codice opera principale : A3486) - Madonna (Ciccone); Madonna (Ciccone); Madonna (Ciccone) (NEW YORK (STATI UNITI) SIRE RECORS INC.)
* LUCKY STAR* BORDERLINE* LIKE A VIRGIN* MATERIAL GIRL* PAPA DON'T PREACH* OPEN YOUR HEART* LA ISLA BONITA* LIKE A PRAYER* EXPRESS YOURSELF* CHERISHTHE FIRST-EVER COMPILATION OF MADONNA'S GREATEST VIDEOS.
"Musica: Madonna (Ciccone) ; "
Madonna
PAL, STEREO
INGLESE
Keywords: VIDEOCLIP -- Codice MATERIA SPICS: 9954